2014
DOI: 10.1007/s11103-014-0237-2
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration-induced endodormancy in crown buds of leafy spurge highlights involvement of MAF3- and RVE1-like homologs, and hormone signaling cross-talk

Abstract: Vegetative shoot growth from underground adventitious buds of leafy spurge is critical for survival of this invasive perennial weed after episodes of severe abiotic stress. To determine the impact that dehydration-stress has on molecular mechanisms associated with vegetative reproduction of leafy spurge, greenhouse plants were exposed to mild- (3-day), intermediate- (7-day), severe- (14-day) and extended- (21-day) dehydration treatments. Aerial tissues of treated plants were then decapitated and soil was rehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 65 publications
(78 reference statements)
2
18
0
Order By: Relevance
“…However, the perennial nature of leafy spurge is attributed to vegetative production from an abundance of UABs that undergo well-defined phases of seasonally induced para-, endo-and ecodormancy , which help optimize distribution of new shoots from the soil bud bank over time . Because dormancy in UABs involves arrested development of the shoot apical meristems (Horvath et al 2003;Horvath and Anderson 2009), similar to that reported in buds of perennial tree species (Cooke et al 2012;Rinne et al 2010;Rohde and Bhalerao 2007), it is a key factor allowing herbaceous perennial weeds to escape many control measures and periods of severe abiotic stress (Anderson et al 2001Doğramacı et al 2014).…”
Section: Dormancy In Underground Adventitious Buds Of Leafy Spurgementioning
confidence: 54%
See 4 more Smart Citations
“…However, the perennial nature of leafy spurge is attributed to vegetative production from an abundance of UABs that undergo well-defined phases of seasonally induced para-, endo-and ecodormancy , which help optimize distribution of new shoots from the soil bud bank over time . Because dormancy in UABs involves arrested development of the shoot apical meristems (Horvath et al 2003;Horvath and Anderson 2009), similar to that reported in buds of perennial tree species (Cooke et al 2012;Rinne et al 2010;Rohde and Bhalerao 2007), it is a key factor allowing herbaceous perennial weeds to escape many control measures and periods of severe abiotic stress (Anderson et al 2001Doğramacı et al 2014).…”
Section: Dormancy In Underground Adventitious Buds Of Leafy Spurgementioning
confidence: 54%
“…However, leafy spurge plants exposed to a RD in temperature alone (RDt; 27 → 10 °C ) under a constant photoperiod of 16 h or a RD in photoperiod alone (RDp; 16-h → 8-h light) at a constant temperature of 26 o C (Foley et al 2009) did not induce endodormancy in UABs. Additionally, exposing leafy spurge plants to 14 days of continuous dehydration induced a transition from para-to endodormancy in UABs (Doğramacı et al 2014), whereas short-term (3 days) dehydration induced growth competence in UABs, which were previously forced into endodormancy by the RDtp treatment (Doğramacı et al 2011).…”
Section: Leafy Spurge As a Model For Studying Well-defined Phases Of mentioning
confidence: 99%
See 3 more Smart Citations